Knowledge, attitudes and practice among healthcare workers towards COVID-19 in a tertiary care centre in north India - Mahajan, Neha; Saroch, Neelisha; Sharma, Pooja; Gupta, Anish (International Journal of Research in Medical Sciences, 2023)
Background: Coronavirus disease pandemic has affected the entire world and till date, there is no definitive cure for it with prevention of infection and knowledge about the disease being the only proven effective methods to contain it. Healthcare workers (HCWs) are highly susceptible to getting infected and their knowledge about COVID-19 infection has been known to be inversely proportional to the rates of COVID-19 infection. Methods: Cross-sectional questionnaire-based study assessing knowledge, attitude and practices towards COVID-19 preventive measures was carried out amongst HCWs at a tertiary care hospital in North India. Results: Around 95% of HCWs had received training regarding COVID-19 infection and more than 95% HCWs had adequate knowledge about COVID-19 infection. More than 95% HCWs experienced anxiety and fear while monitoring and treating COVID-19 patients. 85% HCWs felt that there is sufficient awareness in the society regarding COVID-19 infection. Most of the respondents followed correct practices for avoidance of COVID-19 infection with around 90% respondents using face masks and practicing frequent hand washing. Social distancing and avoidance of large gatherings was practiced by around 95% respondents. More than 95% respondents had either taken COVID-19 vaccine or wish to take it. Conclusions: The study suggested that the majority of HCWs had good knowledge and positive attitude toward COVID-19 but there are still some lacunae present in the knowledge regarding prevention of COVID 19 infection. Further education and training are required for HCWs so as to fight COVID and prevent its spread in a better way.